2009
DOI: 10.2174/138945009787122879
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Sepsis in the Elderly: Clinical Impact and Therapeutic Considerations

Abstract: The aging world population will increase the incidence and mortality of severe sepsis. The aim of the present article is to review the pathophysiological differences in sepsis and its clinical impact on the elderly. The impact of immunosenescence on innate and acquired immunity is associated with relative immunologic depression that may favor the spreading of inflammation. Elderly patients also have enhanced apoptotic pathways that may contribute to the incidence of mortality due to sepsis. The inflammation-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 0 publications
0
36
0
2
Order By: Relevance
“…Interestingly, age was a very strong contributor to mortality even in patients without recorded comorbidities. This could be due to unmeasured or misclassified comorbidities, but another plausible explanation is immunosenescence 30 31. Ageing is associated with changes in both the innate and adaptive immune response, such as an increase in functionally impaired macrophages and a shift from Th1 to Th2 cytokine response 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, age was a very strong contributor to mortality even in patients without recorded comorbidities. This could be due to unmeasured or misclassified comorbidities, but another plausible explanation is immunosenescence 30 31. Ageing is associated with changes in both the innate and adaptive immune response, such as an increase in functionally impaired macrophages and a shift from Th1 to Th2 cytokine response 30.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to unmeasured or misclassified comorbidities, but another plausible explanation is immunosenescence 30 31. Ageing is associated with changes in both the innate and adaptive immune response, such as an increase in functionally impaired macrophages and a shift from Th1 to Th2 cytokine response 30. Interestingly, a recent study reported age-related impairment of alveolar macrophages and Toll-like receptor levels during pneumonia caused by S pneumoniae in mice 32.…”
Section: Discussionmentioning
confidence: 99%
“…In elderly patients, metabolic disorders and cardiac dysfunction are important components of multiorgan failure after sepsis [13][14][15] and are poor prognostic factors for patients with severe sepsis [16]. In septic patients, lactate is recognized as an important metabolic biomarker, as it is produced following cellular conversion from normal aerobic oxidative phosphorylation to abnormal anaerobic metabolism or abnormal aerobic glycolysis following tissue perfusion-induced cellular hypoxia or sepsis-induced immune cell activation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, super low levels of LPS have been detected in circulation of humans and experimental animals with adverse health conditions, including obesity, chronic smoking, infection, and aging (8 -12). Humans with these adverse conditions tend to have elevated mortality associated with septic shock (13,14). Endotoxin priming and exacerbated mortality are also observed in experimental animals (15,16).…”
mentioning
confidence: 99%